Foi Habat Mantra in Elaar Let Village Keci Kecil Timur Selatan District Southeast Maluku Regency: An Ecocriticism Literature - Dian Ayu Ningsi Madubun; Mariana Lewier; Grace Somelok (Universitas Pattimura, 2026)
This study aims to describe one of the forms of old poetry in Maluku, namely the foi habat spells in Elaar Let Village, Kei Kecil Timur Selatan District, Southeast Maluku Regency based on a study of literary ecocriticism. The approach used in this study is a qualitative approach that focuses on the foi habat spells which contains literary ecocriticism. For data collection, the techniques used are observation techniques, interview techniques, recording techniques, field note techniques, and documentation techniques. The data analysis technique in this study uses four stages of data collection, namely, the data collection stage, the data reduction stage, the data presentation stage, and the conclusion drawing stage (verificatin). The results of this study indicate the existence of ecocriticism or the relationship between humans and nature contained in the foi habat mantra, namely good land and environmental management to produce fertile plants, the use of plants planted for human benefit, not using chemicals that can damage or harm the environment when farming, maintaining and protecting the legacy of plants left by ancestors to the next generation, and the results of the plants can be enjoyed by all groups without distinguishing between male or female gender.